Application of divergent split injection in a CIDI diesel engine to reduce emissions and boost the efficiency - Taghavifar, Hadi (Transport, 2019)
The application of single injection in diesel engines has been becoming outdated given the advent of High-Pressure Common Rail (HPCR) system. Multiple injection or split injection presents more controllability over the economic use of fuel during the injection process. In this sense, a thorough investigation of a new concept with the use of divergent injection and split injection is proposed, based on which the whole chamber area was covered with two nozzles of different angles. Moreover, the system allows the optimal use of time span for injection in by assigning different dwell-time periods between injection pulses. The results indicate that increasing the divergence of nozzle angles could possibly bring about arise of Uniformity Index (UI) and Indicated Power (IP) of engine. In contrast, increase of dwell time leads to deterioration of Indicated Mean Effective Pressure (IMEP) and Indicated Specific Fuel Consumption (ISFC). The data points of several injection schemes are presented in IMEP-NOx and ISFC-soot plots in comparison with single injection that shows adoption of a proper injection policy can establish an ideal trade-off between emissions and engine performance.